O entrelaçamento da Geografia com a educação ambiental - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
The science of Geography maintains its historical role, acting in interdisciplinarity, in the most diverse sciences, with intercession between the human, social and natural sciences. In turn, the environment in the construction of its concept, the environment starts to be considered a system, a unit of diverse manifestations with a close relationship with each other, structured and redefined as an organism. From the considerations, the theme presented in this work is the science of geography with environmental education. And as a delimitation of the addressed theme, we present the studies of geography and the impact on the environment. In this context, the problem question that guided this study was raised: how is the intertwining of geography with environmental education? This article resulted from a bibliographical research with a qualitative approach entitled “THE LINKAGE OF GEOGRAPHY AND ENVIRONMENTAL EDUCATION”. The general objective was to understand how the intertwining of geography with environmental education occurs and as specific objectives: Historicize geographic science in the global and national scope; analyze the teaching of geography and discuss geographic science in the context of environmental education. The main authors used in the literature review were: Cavalcanti (2002); Corrêa (2003) and Simplício (1997). As a result, it was found that: as geographical science, it has connections with other sciences, helping to propose public policies aimed at environmental preservation and the environment is inserted in Geography since its unification as a science, until its currents of geographical thought.
Keywords: Ciência Geográfica; Educação Ambiental; Geografia; Meio Ambiente; CNPQ:: CIÊNCIAS HUMANAS